Functional limitations related to foot pain in the elderly - Oliveira, Fabiana Maria Rodrigues Lopes de; Barbosa, Keylla Talitha Fernandes; Albuquerque, Saemmy Grasiely Estrela de; Rodrigues, Mayara Muniz Dias; Santos, Kamyla Félix Oliveira dos; Fernandes, Maria das Graças Melo (Rev Rene, 2015)
Objective: to investigate the association between foot pain and functional disability in the elderly. Methods: descriptive study conducted among the elderly attended in a geriatric outpatient clinic of a university hospital. The sample consisted of 114 elderly who reported foot pain. Data was collected through subsidized interview, using structured instrument, covering demographic variables and the Manchester Foot Pain and Disability Index in Elderly and the Mini Mental State Examination. Results: there was a high incidence of foot pain among women and young elderly as well as significant inability to perform certain daily activities. Conclusion: it is identified the need for special attention to the health of elderly reporting foot pain, since this tends to restrict daily activities, causing decreased quality of life, immobilization and possible episodes of falls.